Efficiency Appraisal Of Yazd University Of Medical Science Hospitals By Quantitative Approach Data Envelopment Analysis(DEA) - Roohollah Askari; Reza Goudarzi; Hossein Fallahzadeh; Bahareh Zarei; Arefeh Dehqani Tafti (Tehran University of Medical Sciences, 2012)
Background and Aim: Paying attention to efficiency of cost and performance in hospitals as the largest and the most costly performing unit of the health care systems is very crucial. This study aimed to assess the efficiency of hospitals related to Yazd University of Medical Sciences (YUMS). Materials and Methods: In this study, the efficiency of Hospitals of YUMS was assessed by Data Envelopment Analysis method during years 2000- 2008. The variables were of two types: output variables including the percentage of occupied beds, inpatient days and the number of surgical procedures and input variables were number of active beds, nurses, medical staff and other personnel. The data was analyzed using Deap2.1 software. Results: Average of technical, management and scale efficiency of hospitals was 0.958, 0.986 and 0.963 respectively. We concluded that the capacity of efficiency promotion in hospitals is increasable up to 5%. In addition, the nurses as one of the most important input variables, had the most apparent slack inputs. Conclusion: Although the level of efficiency was optimal and there was little unused capacity for increasing efficiency in hospitals, however, managers should plan to increase the efficiency. Finally, assessing the effect of variables such as service quality and patient satisfaction on hospitals efficiency is recommended.